Application Potential of Trichoderma in the Degradation of Phenolic Acid-Modified Chitosan - Swiontek Brzezinska, Maria; Kaczmarek-Szczepanska, Beata; Dabrowska, Grazyna B; Michalska-Sionkowska, Marta; Dembinska, Katarzyna; Richert, Agnieszka; Pejchalová, Marcela; Kumar, Sweta Binod; Kalwasinska, Agnieszka (MDPI, 2023)
The aim of the study was to determine the potential use of fungi of the genus Trichoderma for the degradation of phenolic acid-modified chitosan in compost. At the same time, the enzymatic activity in the compost was checked after the application of a preparation containing a suspension of the fungi Trichoderma (spores concentration 10(5)/mL). The Trichoderma strains were characterized by high lipase and aminopeptidase activity, chitinase, and beta-1,3-glucanases. T. atroviride TN1 and T. citrinoviride TN3 metabolized the modified chitosan films best. Biodegradation of modified chitosan films by native microorganisms in the compost was significantly less effective than after the application of a formulation composed of Trichoderma TN1 and TN3. Bioaugmentation with a Trichoderma preparation had a significant effect on the activity of all enzymes in the compost. The highest oxygen consumption in the presence of chitosan with tannic acid film was found after the application of the consortium of these strains (861 mg O-2/kg after 21 days of incubation). Similarly, chitosan with gallic acid and chitosan with ferulic acid were found after the application of the consortium of these strains (849 mgO(2)/kg and 725 mg O-2/kg after 21 days of incubation). The use of the Trichoderma consortium significantly increased the chitinase activity. The application of Trichoderma also offers many possibilities in sustainable agriculture. Trichoderma can not only degrade chitosan films, but also protect plants against fungal pathogens by synthesizing chitinases and beta-1,3 glucanases with antifungal properties.
Aplikační potenciál Trichoderma při degradaci chitosanu modifikovaného kyselinou fenolovou
Keywords: chitosan; Trichoderma; biodegradation; chitosan; Trichoderma; biodegradace